Effectiveness of Rice Husk and Bagasse Fly Ash as Adsorbent of Cr Metal on Batch System - Kharisma Resti Kurnia Diah Sangandita; Budi Utami (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
This study aimed to utilize rice husk and bagasse fly ash as Cr metal adsorbent. In this study, the adsorption used batch system. The steps of research were preparation of materials, activation of materials with HCl and NaOH solutions, characterization test using SEM, FTIR and AAS. Determination of optimum condition of Cr metal adsorption on variation of adsorbent composition, adsorbent mass, adsorbate concentration and isotherm adsorption study. The result showed that the adsorbent of rice husk and bagasse fly ash can be used as adsorbent because there were pores that is based on SEM analysis, based on FTIR results that there were a –OH (hydroxyl) functional group at wavenumber 3424.76 cm-1 and Si-O from Si-O-Si (siloxane) functional group at wavenumber 1048.36 cm-1 in the combination of rice husk and bagasse fly ash adsorbent, based on AAS results it was found that the optimum composition ratio of rice husk and bagasse fly ash adsorbent was 1:2 with the percentage of Cr adsorbed 98.90%, the optimum adsorbent mass at 0.2 g with the percentage of Cr adsorbed 99.77% and the optimum adsorbate concentration at 20.645 mg/L with the percentage of Cr adsorbed 99.63%. The pattern of adsorption isotherm tends followed the Langmuir isotherm which means the adsorption process chemically.